THE CONNECTION OF EMOTIONS WITH THE MENTAL STATE OF HIGHLY QUALIFIED WRESTLERS (Spectrum Journal of Innovation, Reforms and Development, 2023)
The paper considers the aspect of predicting the potential of young athletes in martial arts. The author recommends using genetic markers in case of difficulties. At the same time, the method of dermatoglyphics is of great interest for use in sports selection in the practice of training a sports reserve.